Riscos, uma oportunidade para a reinvenção da vida - Vilhena, Andrea Mello Gouthier de (Revista Econômica do Nordeste, 2016)
GIDDENS, Anthony. A Política da Mudança Climática. Rio de Janeiro: Ed. Zahar, 2010. ISBN 978-85-378-0261-8 7